2008
DOI: 10.1088/1009-0630/10/1/13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sterilizing Effect of Nonequilibrium Atmospheric-Pressure He/O2 and Ar/O2 Plasma Jets

Abstract: The sterilizing effect of the non-equilibrium atmospheric pressure plasma jet by applying it to the Bacillus subtilis spores is invesigated. A stable glow discharge in argon or helium gas fed with active gas (oxygen), was generated in the coaxial cylindrical reactor powered by the radio-frequency power supply at atmospheric pressure. The experimental results indicated that the efficiency of killing spores by making use of an Ar/O2 plasma jet was much better than with a He/O2 plasma jet. The decimal reduction v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For example, when the exposure distance was increased from 0.5 cm to 2 cm in the case of air CAPJ, Pedroni et al (64) observed a reduction in the log colony-forming unit (CFU) reduction value from 2.5 to approximately 1.2. Therefore, the decline in CP's antimicrobial activity with an extended exposure interval, as reported by Pedroni et al (64) and Shouzhe and Jinpyo (63), may be attributed to a decrease in the concentration of active species during CP, as suggested by Lotfy et al (65).…”
Section: Various Factors Affecting the Inactivation Efficacy Of Cp In...mentioning
confidence: 82%
See 1 more Smart Citation
“…For example, when the exposure distance was increased from 0.5 cm to 2 cm in the case of air CAPJ, Pedroni et al (64) observed a reduction in the log colony-forming unit (CFU) reduction value from 2.5 to approximately 1.2. Therefore, the decline in CP's antimicrobial activity with an extended exposure interval, as reported by Pedroni et al (64) and Shouzhe and Jinpyo (63), may be attributed to a decrease in the concentration of active species during CP, as suggested by Lotfy et al (65).…”
Section: Various Factors Affecting the Inactivation Efficacy Of Cp In...mentioning
confidence: 82%
“…The distance between the nozzle of the CAPJ and the sample is a crucial factor that impacts the effectiveness of CP in combating microbes. Studies by Sharma et al (62) and Shouzhe and Jinpyo (63), have shown that increasing the exposure distance leads to a decrease in the antimicrobial effect. For example, when the exposure distance was increased from 0.5 cm to 2 cm in the case of air CAPJ, Pedroni et al (64) observed a reduction in the log colony-forming unit (CFU) reduction value from 2.5 to approximately 1.2.…”
Section: Various Factors Affecting the Inactivation Efficacy Of Cp In...mentioning
confidence: 99%
“…Thus, to have a successful CAP treatment, one should know the gas flow rate at which the most reactive species concentrate. Also, some reports have shown that the antimicrobial efficacy of CAP treatment is decreased by increasing the CAP exposure distance because the concentration of reactive species is reduced as a result of the short lifetime [64,77], meaning that some of them are annihilated before reaching the sample. The other factor that affects antimicrobial efficacy is the CAP treatment time.…”
Section: Wound Sterilization or Wound Disinfection By Cold Plasmamentioning
confidence: 99%